Preliminary Starch Grain Evidence of Ancient Stone Tool Use at the Early Archaic (9,000 B.P.) Site of Sandy Hill, Mashantucket, Connecticut - Thomas C. Hart; Timothy H. Ives (Ethnobiology Letters, 2013)
Early Archaic subsistence strategies of New England remain poorly understood despite their importance in helping researchers understand how people adapt to changing landscapes following the end of the last glacial maximum (21,000-14,000 B.P.). Excavations at the Mashantucket Pequot Reservation in Mashantucket, Connecticut during the 1990s revealed a large, semi-sedentary village nestled alongside a complex wetland ecosystem. In this paper, we present preliminary starch grain analysis of several stone tools recovered and curated from these excavations. The results of this study indicate that both transitory and reserve starch grains are preserved on these artifacts and that at least one of the artifacts may have been used for leaf or stem processing. The results of this study also demonstrate the potential for future research in which paired macrobotanical and residue analysis will allow for a better understanding of subsistence practices at the site and during the early Archaic in general.